Heavy flavour at the Large Hadron Collider - Gibson, Valerie (Physica scripta, 2013)
Heavy flavour physics provides a crucial role in the validation of the Standard Model of particle physics and in the search for new phenomena beyond. This review provides a personal summary of the headline results as of May 2013 from the Large Hadron Collider heavy flavour community in the subject areas of heavy flavour production and spectroscopy, mixing and charge parity violation and rare decays.